Clinical associations between metabolic syndrome and the development of microalbuminuria in Korean men. Issue 3 (March 2015) - Ryoo, Jae-Hong; Chun, Hyejin; Lee, Hong-Soo; Suh, Eunkyung; Choi, Joong-Myung; Kim, Min-Gi; Shin, HoCheol; Park, Sung Keun; Oh, Chang-Mo; Ko, Taeg Su
Abstract Aims There have been several studies on the association between metabolic syndrome (MetS) and microalbuminuria. However, none has examined whether MetS is associated with the prospective development of microalbuminuria. Accordingly, we performed a prospective study to evaluate the longitudinal effects of baseline number of MetS traits on the development of microalbuminuria in Korean men. Methods 1649 Korean men without microalbuminuria in 2005 were included and followed prospectively until 2010 with the endpoint being the development of microalbuminuria. MetS was defined according to the joint interim statement of the International Diabetes Federation Task Force on Epidemiology and Prevention. Microalbuminuria was evaluated by urine albumin creatinine ratio (UACR). Risk estimations for development of microalbuminuria were analyzed according to the number of MetS traits using multivariate adjusted Cox proportional hazards model. Results During 5611.8 person-years of follow-up (median 3.40 ± 1.46 years), microalbuminuria developed in 91 (5.5%) participants between 2006 and 2010. After adjusting for multiple covariates, the hazard ratios (95% confidence interval) for development of microalbuminuria comparing 1, 2 and 3–5 MetS traits vs 0 were 2.57 (0.97–6.82), 2.94 (1.09–7.98) and 3.85 (1.37–10.86), respectively. Conclusions The number of MetS traits independently associated with the future development of microalbuminuria during the 5-year follow-up period, and MetS per se was an independent risk factor for microalbuminuria.